INTEGRATED DESIGN OF KNOWLEDGE DIMENSIONS AND THINKING PROCESS LEVEL ON MEASUREMENT MATERIALS FOR HIGH SCHOOL PHYSICS LEARNING - Hanifah Ahmad; Amali Putra; - Hidayati; Renol Afrizon (Universitas Negeri Padang, 2021)
The learning objectives in the 2013 Curriculum expect changes and improvements in students' competencies. To encourage the achievement of these learning objectives, the learning tools should refer to the Graduate Competency Standards (SKL) which have been regulated in Permendikbud number 20 of 2016. It is explained that the revised Bloom's taxonomy is a reference in developing SKL. The revised Bloom's Taxonomy developed by Anderson and Krathwohl in 2001 categorizes learning outcomes by referring to the dimensions of knowledge and levels of thinking processes. However, the reality is that the intensity of the dimensions of knowledge and the level of thinking processes in learning devices is still not balanced. So, the learning objectives can not be achieved optimally. This study aims to produce a design in the form of a learning device that is oriented to the integration of the dimensions of knowledge and the level of thinking processes. The type of research used is R & D (Research and Development) using a development model, namely the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. In this study, it was only limited to the third stage with valid criteria. The results showed that the learning tools oriented to the integration of the dimensions of knowledge and the level of thought processes were in the very valid category with an overall average value of 3.38